Incidence and prevalence of papillary carcinoma of thyroid gland in Al- muthana province - Dr.Imad Diame AL-Hasani; Dr.Haider Kudair Abd (International Journal of Medical Toxicology and Legal Medicine, 2024)
This investigation was conducted for Incidence and Prevalence of papillary carcinoma in AL-Muthana provinces (2019 – 2023). Total No. of cases 372 with papillary carcinoma in AL-Muthana provinces were used in this study. The demographical data were taken from all patients. The results showed that 49.5% from cases were non neoplastic and 50.5% were with neoplastic case. The carcinoma was recorded significantly higher in Female (88%) than male (12%), and the age between 21-40 years were most dominant. The current results exhibited that malignant cases according to With LN. were 24% and With Out LN involvement were 76%. The Classification of Malignant without LN cases according to histopathological diagnosis showed that 18% with Follicular carcinoma and 82% with Papillary carcinoma, while with LN involvement showed 11% Papillary microcarcinoma and 89% were with Papillary carcinoma. In conclusion, the Papillary carcinoma was highly incidence in ALMuthana provinces at (2019 – 2023).